1990
DOI: 10.1007/bf02341026
|View full text |Cite
|
Sign up to set email alerts
|

Control of photosynthesis in leaves as revealed by rapid gas exchange and measurements of the assimilatory force FA

Abstract: The rapid transients of CO2 gas exchange have been measured in leaves ofHelianthus annuus L. In parallel experiments the assimilatory force FA, which is the product of the phosphorylation potential and the redox ratio NADPH/NADP, has been calculated from measured ratios of dihydroxyacetone phosphate to phosphoglycerate in the chloroplast stroma and in leaves. The following results were obtained: (i) When the light-dependent stroma alkalization was measured under steady-state conditions for photosynthesis in ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
4
27
1
Order By: Relevance
“…22 and 23). Under most conditions, high intensity illumination does not lead to complete reduction of Q A in PS II, indicating that light input is decreased as electron transfer nears saturation (23 25), implying that output from the light reactions and its consumption by the Calvin cycle are tightly coregulated. Furthermore, the pH of the lumen appears to be tightly regulated to a narrow range, where the stabilities of luminal components and the effective rate constants for electron transfer are near optimal (1).…”
mentioning
confidence: 99%
“…22 and 23). Under most conditions, high intensity illumination does not lead to complete reduction of Q A in PS II, indicating that light input is decreased as electron transfer nears saturation (23 25), implying that output from the light reactions and its consumption by the Calvin cycle are tightly coregulated. Furthermore, the pH of the lumen appears to be tightly regulated to a narrow range, where the stabilities of luminal components and the effective rate constants for electron transfer are near optimal (1).…”
mentioning
confidence: 99%
“…In the simulations used for Figure 5 . These values are in agreement with some estimations of free Pi in the stroma (Hampp et al, 1982;Sharkey and Vanderveer, 1989;Siebke et al, 1990), although other estimations result in values an order of magnitude higher (Dietz and Heber, 1984;Prinsley et al, 1986a). …”
Section: Electrochromic Shiftsupporting
confidence: 81%
“…Reported values of ADP/ATP in chloroplasts, across different irradiance and [CO2] levels are always higher than 0.35 (Hampp et al, 1982;Dietz and Heber, 1984;Prinsley et al, 1986a;Siebke et al, 1990;Heineke et al, 1991), whereas ATP/ADP/Pi remained lower than 1000 M −1 (Giersch et al, 1980;Siebke et al, 1990), so regulation of ATPase activity by low ADP concentrations may not occur in vivo (Kanazawa and Kramer, 2002). The underestimation of ADP/ATP by the model may be the result of the parameter values chosen for regulation of Rubisco activase (Section 5.2.7.1) or consumption by the Calvin cycle in the regeneration of RuBP (Section 5.2.7.2).…”
Section: Electrochromic Shiftmentioning
confidence: 99%
“…Estimations from experimental data indicated that Pi is expected to remain , 10 mM (Hampp et al, 1982;Sharkey and Vanderveer, 1989;Siebke et al, 1990), though the uncertainty on these estimations was not reported by the authors, even though assumptions on chloroplast volume or total chloroplast phosphate content were often required. This means that Pi could also contribute to the regulation of ATPase conductance, pmf, and NPQ at a wide range of light intensities and CO 2 levels, even when Pi does limit CO 2 assimilation.…”
Section: The Role Of Inorganic Phosphate In the Regulation Of The Elementioning
confidence: 96%